2023
DOI: 10.3389/fonc.2023.1246716
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the first-line treatment for metastatic colorectal cancer

Sara Cherri,
Ester Oneda,
Laura Zanotti
et al.

Abstract: Colorectal cancer represents an important oncological challenge both for its incidence, which makes it an important health problem, and for its biological complexity, which has made clinical results very difficult in terms of outcome for this category of patients. To date these diseases should not be treated as a single entity but it is necessary to distinguish colorectal cancers based on characteristics that nowadays are essential to have greater therapeutic benefits. These include the sideness of the disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 100 publications
0
1
0
Order By: Relevance
“…The first in-human trial of binimetinib identified 60 mg twice daily (BID) as the maximum tolerated dose (MTD) and 45 mg BID as the recommended phase 2 dose (RP2D) for binimetinib monotherapy in patients with BRAF-mutant CRC [ 16 ]. Preliminary results indicate that binimetinib treatment in combination with ICIs has encouraging activity and acceptable tolerability in patients with MSS mCRC [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The first in-human trial of binimetinib identified 60 mg twice daily (BID) as the maximum tolerated dose (MTD) and 45 mg BID as the recommended phase 2 dose (RP2D) for binimetinib monotherapy in patients with BRAF-mutant CRC [ 16 ]. Preliminary results indicate that binimetinib treatment in combination with ICIs has encouraging activity and acceptable tolerability in patients with MSS mCRC [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%